2022
DOI: 10.1089/ten.tea.2021.0226
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Hydrogels for Articular Cartilage and Nucleus Pulposus Repair: Status Quo and Prospects

Abstract: Osteoarthritis (OA) and chronic low back pain due to degenerative (intervertebral) disc disease (DDD) are two of the major causes of disabilities worldwide, affecting hundreds of millions of people and leading to a high socioeconomic burden. Although OA occurs in synovial joints and DDD occurs in cartilaginous joints, the similarities are striking, with both joints showing commonalities in the nature of the tissues and in the degenerative processes during disease. Consequently, repair strategies for articular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 155 publications
1
14
0
Order By: Relevance
“…Mesenchymal stromal cells (MSCs) have shown interesting results in the field of cartilage regeneration, mainly due to their accessibility, immunomodulatory and pro-regenerative capabilities, and chondrogenic differentiation potential [ 32 , 33 , 34 , 35 ]. It has been shown that MSCs from various origins, combined with scaffold materials, have great potential in the regeneration of cartilage, in both animal models and in humans, as suggested by recent clinical trials [ 27 , 28 , 30 , 36 ]. It has been recognized that MSCs, laden in natural or synthetic hydrogels, create a suitable environment for inducing their cellular differentiation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSCs) have shown interesting results in the field of cartilage regeneration, mainly due to their accessibility, immunomodulatory and pro-regenerative capabilities, and chondrogenic differentiation potential [ 32 , 33 , 34 , 35 ]. It has been shown that MSCs from various origins, combined with scaffold materials, have great potential in the regeneration of cartilage, in both animal models and in humans, as suggested by recent clinical trials [ 27 , 28 , 30 , 36 ]. It has been recognized that MSCs, laden in natural or synthetic hydrogels, create a suitable environment for inducing their cellular differentiation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of injectable hydrogels in cartilage regeneration is considered a promising strategy due to the minimally invasive procedure [ 8 , 28 ]. In situ gelation enables the formed hydrogel to quickly set its volume, adapt to the shape of the defect, and establish an efficient integration with the host tissue [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, various new biomedical materials and strategies have been used for local treatment and to promote the regeneration of damaged tissues [33][34][35][36]. Here, we built an OPF/SMA hydrogel scaffold formed in situ, combined with PLGA microspheres of different specifications to achieve the purpose of timed slow release.…”
Section: Fabrication and Characterization Of Opf/sma Composite Hydrog...mentioning
confidence: 99%